Spatial Audio Object Coding With Enhanced Audio Object Separation - Falch, Cornelia; Terentiev, Leonid; Herre, Jürgen (Proceedings of the 13th International Conference on Digital Audio Effects (DAFx-10), 2010)
Spatial sound reproduction on a multi-channel loudspeaker setup indicate a consistent trend in today's audio playback systems. Digital surround sound significantly improves the realism of the spatial sound experience, but also results in a drastic increase in required audio data rate. Spatial Audio Coding (SAC) technology provides means for efficient storage and transmission of multi-channel signals by a down-mix signal and associated parametric side information describing the spatial sound image. More recently, SAC has been extended with an object-based concept termed Spatial Audio Object Coding (SAOC) enabling efficient coding and interactive spatial rendering of multiple individual audio objects at the playback side. Due to the underlying parametric coding approach, object level manipulations may affect the produced perceptual sound scene quality, and using extreme object attenuation or boosting may result in unacceptably de-graded audio quality. The paper describes how regular SAOC processing is advanced to ensure high quality sound reproduction even in demanding remix applications.
herre_papers_spatial_audio_coding_and_3d_audio_coding